Calcification and latitudinal distribution of extant coccolithophores across the Drake Passage during late austral summer 2016 - Saavedra-Pellitero, Mariem; Baumann, Karl-Heinz; Fuertes Prieto, Miguel ?ngel; Schulz, Hartmut; Marcon, Yann; Vollmar, Nele Manon; Flores Villarejo, Jos? Abel; Lamy, Frank (Biogeosciences, 2019)
[EN]Coccolithophores are globally distributed microscopic marine algae that exert a major influence on the global carbon cycle through calcification and primary productivity. There is recent interest in coccolithophore polar communities; however field observations regarding their biogeographic distribution are scarce for the Southern Ocean (SO). This study documents the latitudinal, as well as in depth, variability in the coccolithophore assemblage composition and the coccolith mass variation in the ecologically dominant Emiliania huxleyi across the Drake Passage. Ninetysix water samples were taken between 10 and 150m water depth from 18 stations during POLARSTERN Expedition PS97 (February?April 2016). A minimum of 200 coccospheres per sample were identified in the scanning electron microscope, and coccolith mass was estimated with light microscopy. We find that coccolithophore abundance, diversity and maximum depth habitat decrease southwards, marking different oceanographic fronts as ecological boundaries. We characterize three zones: (1) the Chilean margin, where E. huxleyi type A (normal and overcalcified) and type R are present; (2) the Subantarctic Zone (SAZ), where E. huxleyi reaches maximum values of 212.5 ? 103 cells L-1 and types B/C, C and O are dominant; and (3) the Polar Front Zone (PFZ), where E. huxleyi types B/C and C dominate. We link the decreasing trend in E. huxleyi coccolith mass to the poleward latitudinal succession from the type A to the type B group. Remarkably, we find that coccolith mass is strongly anticorrelated to total alkalinity, total CO2, the bicarbonate ion and pH. We speculate that low temperatures are a greater limiting factor than carbonate chemistry in the Southern Ocean. However, further in situ oceanographic data are needed to verify the proposed relationships.We hypothesize that assemblage composition and calcification modes of E. huxleyi in the Drake Passage will be strongly influenced by the ongoing climate change. Supported by the Deutsche Forschungsgemeinschaft ...